Gilabert on the Feasibility of Global Justice - Macleod, Colin (Les ateliers de l'éthique / The Ethics Forum, 2013)
In this article, I discuss the analysis of the feasibility of global justice developed by Pablo Gilabert in his recent book From Global Poverty to Global Equality: A Philosophical Exploration. Gilabert makes many valuable contributions to this topic and I agree with most of his analysis. However, I identify a distinction between strategic justification and moral justification that Gilabert neglects. I show how this distinction is useful in addressing objections to the feasibility of global justice. I also claim that Gilabert makes some problematic assumptions concerning the way in which global justice is morally demanding.